The f3’5’h (d) gene for pink coloring of flax flowers is a member of the CYP75 family within the CYP450 gene class: from class function to gene function - A. A. Slobodkina; A. V. Pavlov; E. A. Porokhovinova (Труды по прикладной ботанике, генетике и селекции, 2025)
The publication characterizes flavonoids – plant pigments, their role, classification, and biosynthesis. Attention is mainly paid to the enzymes of the cytochrome P450 class, which, in addition to their participation in flavonoid biosynthesis, play a major role in many other processes, such as polymer biosynthesis, hormone metabolism, and defense against unfavorable factors. Various information about the flavonoid 3’,5’-hydroxylase (F3’5’H) gene is presented, highlighting key advances and major problems in its study. The role of this gene in anthocyanin biosynthesis is discussed, its product is shown to belong to the CYP75 enzyme family from the CYP71 clan of cytochromes P450, and the active centers of the enzyme are displayed.Flax usually has a blue corolla, and delphinidin as the main pigment in its coloration. In this publication, we characterized the d gene (f3’5’h), which in recessive condition causes pink flower coloration and pelargonidin as the main pigment. It was shown that F3’5’H in flax belongs to CYP75 enzymes, but unlike most others is attributed to the CYP75B subfamily rather than CYP75A. The possibility of multiple allelism of F3’5’H leading to different phenotypes was demonstrated, which confirms the multiple allelism of the d gene in flax, already known at the formal genetic level. At present, flax is the only species wherein the emergence of F3’5’H activity went to the detriment of F3’H, probably because flax is phylogenetically distant from other ancient cultivated plants and its evolution is associated with selection for yellow seed color.